Power System Switching Transient Detection using Wavelet Transformed Based Signal Decomposition - Alam, M Shafiul; Chowdhury, Md Shamimul Haque; Uddin, Muhammad Athar (IIUC Studies, 2012)
Switching transient phenomena in Electric Power System develop several disturbances, sometimes very hazardous for the electrical equipment life, for the environment and for the human life. Switching transient phenomena produce over voltage, over current and electrical fields, which haven't to neglect. Several types of wavelet network algorithms have been considered for detection of power system switching transients. But both time and frequency information are accessible by multiresolution analysis (MRA). This paper presents a wavelet transform based multiresolution analysis of power system signal to detect, localize and extract switching transients. Power system switching transients have been simulated using MATLAB-7.01. The key idea underlying the approach is to decompose a distorted signal into other signals which represents a smoothed version and detailed version of the original signal. The decomposition is performed using multiresolution analysis. The proposed method appears to be robust for detection and localization of power quality disturbances produced due to load switching and capacitor switching. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12270 IIUC Studies Vol.7 2011: 241-248